Case Report: Four cases of SARS-CoV-2-associated Guillain-Barré Syndrome with SARS-CoV-2-positive cerebrospinal fluid detected by metagenomic next-generation sequencing: a retrospective case series from China - Guan, Yalin; Yu, Changshen; Fei, Yunhan; Wang, Qiushi; Wang, Pan; Zuo, Wenchao; Wu, Hao; Qi, Xuemei; Shi, Qiyun (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is often absent or at low levels in the cerebrospinal fluid (CSF) of patients with previous SARS-CoV-2-associated Guillain-Barré syndrome (GBS). This has led to speculation that SARS-CoV-2-associated GBS is more likely mediated by post-infectious immunity or a parainfection. This understanding has influenced the development of treatment regimens for SARS-CoV-2-associated GBS. This paper reports our experience with four Chinese patients with SARS-CoV-2-associated GBS who tested positive for SARS-CoV-2 RNA in the CSF. They developed symptoms of peripheral nerve damage 4-15 days after fever and confirmed SARS-CoV-2 infection, all of whom presented with progressive weakness of both lower limbs; three with autonomic nerve function impairment such as constipation and urination disorder; and one with polycranial neuritis and Miller-Fisher syndrome. Three patients were tested for anti-ganglioside antibodies, and one tested positive for GD1a-IgG. Four patients recovered well after treatment with anti-viral drugs combined with intravenous immunoglobulin. The present results showed that SARS-CoV-2 RNA can be detected via mNGS in the CSF of some patients with SARS-CoV-2-associated GBS, suggesting that SARS-CoV-2-associated GBS may have